Yeast Kluyveromyces lactis as host for expression of the bacterial lipase: cloning and adaptation of the new lipase gene from Serratia sp. (1st October 2015) - Šiekštelė, Rimantas; Veteikytė, Aušra; Tvaska, Bronius; Matijošytė, Inga
Abstract: Many microbial lipases have been successfully expressed in yeasts, but not in industrially attractive Kluyveromyces lactis, which among other benefits can be cultivated on a medium supplemented with whey––cheap and easily available industrial waste. A new bacterial lipase from Serratia sp. was isolated and for the first time expressed into the yeast Kluyveromyces lactis by heterologous protein expression system based on a strong promoter of Kluyveromyces marxianus triosephosphate isomerase gene and signal peptide of Kluyveromyces marxianus endopolygalacturonase gene. In addition, the bacterial lipase gene was synthesized de novo by taking into account a codon usage bias optimal for K. lactis and was expressed into the yeast K. lactis also. Both resulting strains were characterized by high output level of the target protein secreted extracellularly. Secreted lipases were characterized for activity and stability.